Beneficiation of phosphate ore - Kawatra, S. K. (Society for Mining, Metallurgy, and Exploration, 2013)
Beneficiation of Phosphate Ore examines various methods for processing phosphate rock, an important mineral commodity used in the production of phosphoric acid. The majority of phosphoric acid is produced by the wet process, in which phosphate rock is reacted with sulfuric acid to produce phosphoric acid and gypsum (calcium sulfate dihydrate). This wet process demands a phosphate rock feed that meets certain specifications to produce phosphoric acid efficiently and economically.